Climate adaptation as strategic urbanism: assessing opportunities and uncertainties for equity and inclusive development in cities. (February 2017) - Chu, Eric; Anguelovski, Isabelle; Roberts, Debra
Abstract: An increasing number of cities are recognising the impacts of climate change on their development pathways. In this paper, we assess strategic climate adaptation actions in the cities of Durban (South Africa), Indore (India), and Medellin (Colombia), and examine different approaches to integrating emerging adaptation priorities into urban plans, programmes, or governance arrangements. We highlight sources of planning tension – particularly between aspects of the planning process and larger urban political economic forces – that reshape how subsequent adaptation interventions are framed and implemented. We find that when advanced with a focus on alignment with development, strategic actions that transcend individual actor or sectoral interests have a better chance at taking root. However, we note that a procedural focus in strategic urbanism must also be accompanied by an integrated assessment of planning outcomes in order to ensure more equitable and inclusive development in cities. Although strategic approaches may facilitate coherent policy framings, targeted actor coalitions, and opportunities for collaborative action, such approaches are often unable to adequately capture the difficult policy trade-offs or contestations that are required to further overall adaptive capacities of cities. In other words, strategic adaptation actions must be considered in relation to the powerful, and often entrenched, political economic interests that constrain urban equity at-large. Highlights: Cities are recognising the impacts of climate change on development. We assess strategic adaptation actions in Durban, Indore, and Medellin. Strategic adaptation planning processes can transcend actor or sectoral interests. Strategic plans must also include an integrated assessment of all adaptation outcomes. Strategic actions are often unable to facilitate political economic restructuring in cities.